Ahli waris budaya dunia : menjadi Indonesia, 1950-1965 - Lindsay, Jennifer, Dr.; Liem, Maya H. T. 1957- (Pustaka Larasan ; KITLV-Jakarta, 2011)
History of Indonesian culture, 1950-1965; collection of articles.